Technological Pedagogical and Content Knowledge (TPACK) Abilities of Early Childhood Education Teachers in Digital-Based Learning - Mala, Lilik Sofwatul; Hibana, Hibana; Divanti, Adhelia Imel (Lectura : Jurnal Pendidikan, 2025)
The digital era has significantly transformed the educational landscape, including at the Early Childhood Education (Pendidikan Anak Usia Dini/PAUD) level, where teachers are expected to master content, pedagogy, and technology integration. However, many PAUD teachers still face challenges in effectively combining these three aspects in their teaching practices. This study aims to describe the Technological Pedagogical and Content Knowledge (TPACK) competency level of PAUD teachers in digital-based learning. Using a quantitative descriptive approach, the study involved six teachers from three Raudhatul Athfal (RA, Islamic early childhood education institutions) in Butuh District, Purworejo Regency. Data were collected through observation and documentation using instruments that covered seven TPACK dimensions: Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), and the comprehensive TPACK. The findings revealed that the overall TPACK mastery of PAUD teachers was in the good category, with an average score of 84.44%. The highest-scoring dimension was the integrated TPACK, while the lowest was PCK, indicating a need for improvement in objectively assessing children’s learning processes and outcomes. These results highlight the ability of RA teachers to integrate technology, pedagogy, and content in digital-based learning and underscore the importance of continuous training and mentoring to enhance their TPACK competencies in meeting the demands of 21st-century education.